Functional Consequences of the Disturbances in the GABA-Mediated Inhibition Induced by Injuriesin the Cerebral Cortex - Barbara Imbrosci; Thomas Mittmann (Neural Plasticity)
Cortical injuries are often reported to induce a suppression of the intracortical GABAergic inhibition in the surviving, neighbouring neuronal networks. Since GABAergic transmission provides the main source of inhibition in the mammalian brain, this condition may lead to hyperexcitability and epileptiform activity of cortical networks. However, inhibition plays also a crucial role in limiting the plastic properties of neuronal circuits, and as a consequence, interventions aiming to reestablish a normal level of inhibition might constrain the plastic capacity of the cortical tissue. A promising strategy to minimize the deleterious consequences of a modified inhibitory transmission without preventing the potential beneficial effects on cortical plasticity may be to unravel distinct GABAergic signaling pathways separately mediating these positive and negative events. Here, gathering data from several recent studies, we provide new insights to better face with this “double coin” condition in the attempt to optimize the functional recovery of patients.